STUDY OF THE EFFECT OF RETURN ON ASSET, TANGIBILITY AND BUSINESS RISK ON CAPITAL STRUCTURE - Triherawati, Desi; Nusraningrum, Dewi (Universitas Mercu Buana, 2021)
This study aims to analyze the effect of return on asset, tangibility and business risk on capital structure in Indonesian food and beverage companies in 2014 - 2019. Population in this study is 15 Indonesian food and beverage companies. The sample in this study is 10 Indonesian food and beverage companies. The sampling method for this study is purposive sampling. This study is using Panel Data Regression as the method for data analysis. This study proves that return on asset has negative and not significant effect to capital structure, tangibility has negative and significant effect to capital structure and business risk has negative and significant effect to capital structure.